Paraspeckles interact with SWI/SNF subunit ARID1B to regulate transcription and splicing. (10th November 2022) - Reddy, Divya; Bhattacharya, Saikat; Levy, Michaella; Zhang, Ying; Gogol, Madelaine; Li, Hua; Florens, Laurence; Workman, Jerry L
Abstract: Paraspeckles are subnuclear RNA–protein structures that are implicated in important processes including cellular stress response, differentiation, and cancer progression. However, it is unclear how paraspeckles impart their physiological effect at the molecular level. Through biochemical analyses, we show that paraspeckles interact with the SWI/SNF chromatin‐remodeling complex. This is specifically mediated by the direct interaction of the long‐non‐coding RNA NEAT1 of the paraspeckles with ARID1B of the cBAF‐type SWI/SNF complex. Strikingly, ARID1B depletion, in addition to resulting in loss of interaction with the SWI/SNF complex, decreases the binding of paraspeckle proteins to chromatin modifiers, transcription factors, and histones. Functionally, the loss of ARID1B and NEAT1 influences the transcription and the alternative splicing of a common set of genes. Our findings reveal that dynamic granules such as the paraspeckles may leverage the specificity of epigenetic modifiers to impart their regulatory effect, thus providing a molecular basis for their function. Synopsis: The lncRNA NEAT1 of paraspeckles interacts with the ARID1B subunit of the cBAF type SWI/SNF complex to regulate the expression and alternative splicing of various genes. This interaction might enable paraspeckles to gain target specificity essential for mediating their gene regulatory function. Paraspeckle proteins preferentially bind to the cBAF‐type SWI/SNF complex ARID1B of SWI/SNF and NEAT1 of paraspeckles play a key role in this interaction. ARID1 paralogs have non‐overlapping protein interactions and effects on the transcriptome. Abstract : The lncRNA NEAT1 of paraspeckles interacts with the ARID1B subunit of the cBAF‐type SWI/SNF complex to regulate the expression and alternative splicing of various genes. This interaction might enable paraspeckles to gain target specificity essential for mediating their gene regulatory function.